PROFILE AND PREVENTABILITY OF NEONATAL DEATHS IN A CITY IN LEGAL AMAZON - Kátia Fernanda Alves Moreira; Bianca Oyola Bicalho; Luanna Cristina Sales Santos; Fabíola Mara Gonçalves de Siqueira Amaral; Nathalia Halax Orfão; Mônica Pereira Lima Cunha (Universidade Federal do Paraná, 2017)
Describe the profile of neonatal deaths and preventable causes in Porto Velho, state of Rondônia, in the period from 2011 to 2015. It is a descriptive, cross-sectional study conducted with data from the Sistema de Informação de Nascidos Vivos (Live Births Information System) and Sistema de Informação de Mortalidade (Mortality Information System). Two-hundred and seventy-nine deaths were eligible, with 208 (74.55%) premature births, 156 (55.91%) male, 194 (69.54%) weighing up to 2,499 grams, with Apgar values ranging from 6 to 10 in the first minute (170; 60.93%) and fifth minute (226; 81%); and 261 without anomalies (93.55%). The neonatal mortality coefficient decreased in years 2014 (3.79) and 2015 (2.28). Regarding basic causes, 87 (31.18%) were reducible through adequate attention to newborns, followed by 47 (16.85%) reducible through adequate attention to women during pregnancy. The high prevalence of these deaths calls attention to the need to improve prenatal care and the structure of the Rede Cegonha (Stork Network) in order to ensure care that has quality and is integrated and continuous for mother and children.